Fast and efficient electrochemical thinning of ultra-large supported and free-standing MoS2 layers on gold surfaces. Issue 18 (7th April 2022) - de Freitas, Nicolli; Florindo, Bianca R.; Freitas, Vitória M. S.; Piazzetta, Maria H. de O.; Ospina, Carlos A.; Bettini, Jefferson; Strauss, Mathias; Leite, Edson R.; Gobbi, Angelo L.; Lima, Renato S.; Santhiago, Murilo
Abstract : The same electrochemical process drives the preparation of supported and free-standing molybdenum disulfide monolayers. Abstract : Molybdenum disulfide (MoS2 ) is a very promising layered material for electrical, optical, and electrochemical applications because of its unique and outstanding properties. To unlock its full potential, among different preparation routes, electrochemistry has gain interest due to its simple, fast, scalable and simple instrumentation. However, obtaining large-area monolayer MoS2 that will enable the fabrication of novel electronic and electrochemical devices is still challenging. In this work, we reported a simple and fast electrochemical thinning process that results in ultra-large MoS2 down to monolayer on Au surfaces. The high affinity of MoS2 by Au surfaces enables the removal of bulk layers while preserving the first layer attached to the electrode. With a proper choice of the applied potential, more than 90% of the bulk regions can be removed from large-area MoS2 crystals, as confirmed by atomic force microscopy, photoluminescence, and Raman spectroscopy. We further address a set of contributions that are helpful to elucidate the features of MoS2, namely, the hyphenation of electrochemistry and optical microscopy for real-time observation of the thinning process that was revealed to occur from the edges to the center of the flake, an image treatment to estimate the thinning area and thinning rate, and the preparation of free-standing MoS2 layers by electrochemically thinning bulk flakes on microhole-structured Ni/Au meshes.